Relevansi Antara Puasa Dengan Kesehatan Fisik Pada Remaja - Dewi, Dian Kusuma; Priyanti, Septiani Olive; Alam, Dede Rubai Misbahul; Darwis, Darwis (Turabian: Jurnal Pendidikan Islam, 2024)
Fasting is the restraint of hunger and thirst that is carried out in every month of Ramadhan by running it from dawn to sunset. Fasting must be carried out with serious intentions for a Muslim servant who obeys Allah ta’ala. In addition to enduring hunger and thirst, fasting also has an impact on not doing things that are prohibited such as committing adultery and can also make fasting makruh by saying harsh words or getting angry. This article uses the literature method by researching and reviewing from many sources. There are so many benefits of fasting, one of which is on human health and studies have recognized that fasting makes humans healthier and fitter. The research states that our stomach needs rest to process the rest of the food. Therefore, fasting becomes one time for the stomach does not work all the time and as well as other organs that need rest to improve the quality of functions for the heart and brain. The results show that fasting can be benefical for human physical health, especially for teenagers.